Salmonella in Pig Farms and on Pig Meat in Suriname - Patrick Butaye; Iona Halliday-Simmonds; Astrid Van Sauers (MDPI AG, 2021)
Salmonella is one of the most important food borne zoonotic pathogens. While mainly associated with poultry, it has also been associated with pigs. Compared to the high-income countries, there is much less known on the prevalence of Salmonella in low- and middle-income countries, especially in the Caribbean area. Therefore, we investigated the prevalence of Salmonella in pigs and pig meat in Suriname. A total of 53 farms and 53 meat samples were included, and Salmonella was isolated using standard protocols. Strains were subjected to whole genome sequencing. No Salmonella was found on pig meat. Five farms were found to be positive for Salmonella, and a total of eight different strains were obtained. Serotypes were S. Anatum (n = 1), S. Ohio (n = 2), a monophasic variant of S. Typhimurium (n = 3), one S. Brandenburg, and one S. Javaniana. The monophasic variant of S. Typhimurium belonged to the ST34 pandemic clone, and the three strains were very similar. A few resistance genes, located on mobile genetic elements, were found. Several plasmids were detected, though only one was carrying resistance genes. This is the first study on the prevalence of Salmonella in pigs in the Caribbean and that used whole genome sequencing for characterization. The strains were rather susceptible. Local comparison of similar serotypes showed a mainly clonal spread of certain serotypes.